Women and Crime in Post-Transitional South African Crime Fiction A Study of Female Victims, Perpetrators and Detectives - Binder, Sabine (Costerus New Series, 2020)
In this ground-breaking study, Sabine Binder analyses the complex ways in which female crime fictional victims, detectives and perpetrators in South African crime fiction resonate with widespread and persistent real crimes against women in post-apartheid South Africa. Drawing on a wide range of crime novels written over the last decade, Binder emphasises the genre's feminist potential and critically maps its political work at the intersection of gender and race. Her study challenges the perception of crime fiction as a trivial genre and shows how, in South Africa at least, it provides a vibrant platform for social, cultural and ethical debates, exposing violence, misogyny and racism and shedding light on the problematics of law and justice for women faced with crime. Readership: All interested in crime fiction and its gender/racial political potential, its cultural relevance, its ethics and aesthetics, in South Africa and beyond.